IMPLANTACIÓN DE LA CONTABILIDAD COMERCIAL Y APLICACIÓN DE INDICADORES FINANCIEROS PARA EL COMERCIAL MULTICENTER DEL CANTÓN YANTZAZA PROVINCIA DE ZAMORA CHINCHIPE PERÍODO DEL 1RO. DE ENERO AL 30 DE JUNIO DE 2014 - Poma Palta, Adriana Mariel (2015)
The present denominated thesis work "INSTALLATION OF THE COMMERCIAL ACCOUNTING AND APPLICATION OF FINANCIAL INDICATORS FOR THE COMMERCIAL MULTICENTER OF THE CANTON YANTZAZA COUNTY DE ZAMORA CHINCHIPE PERIOD OF JANUARY 01 AT JUNE 30 THE 2014", it consists on elaborating procedures and countable applications for the System of Multiple Bill that you/they allow to know with accuracy and consistency the handling of the financial-economic situation of the company, with the presentation of the States Financiers. You guides in the execution of the specific objectives where: it was elaborated a plan and specific manual of bills and chord to the necessities of the company, it was designed registrations and countable books for the appropriate operation of the company. Considering the documentation source provided by the proprietor of the warehouse, the countable process was applied leaving of the Initial Inventory, State of Initial Situation, and with it to elaborate auxiliary documents as they are: Auxiliary of Purchases and Sales, Bills to Get paid and to Pay, bank reconciliations; as well as Lists of Payment and Social Provisions, the Daily Book, bigger Book, Balance of Confirmation was elaborated, Leaf of Work with its respective adjustments until ending up obtaining the States Financiers under the 5 International Norms of Accounting, with the purpose of knowing the economic and financial position of the company. Finally it was applied financial indicators of liquidity, indebtedness and profitability which helped to evaluate the financial and operational acting of the company, and this way to facilitate the appropriate one taking of decisions on the part of the proprietor. As for the used methodology it is presented the methods that were applied and that they helped to the theoretical knowledge and I develop I practice, being constituted in the fundamental part for the execution of the proposed objectives. You culminates with the presentation of the respective conclusions and recommendations focused to improve the current position of the company, among those that stands out the correct application of a countable process and application of financial indicators carried out in the company study object, and this way to have an appropriate countable system to continue with the development of the commercial accounting for the following periods. It is recommended the proprietor to continue applying the proposed present, in such a way that he/she can administer himself appropriately the business and to obtain better financial yields that allow to stay in the market.